DPSCs Attenuate Experimental Progressive TMJ Arthritis by Inhibiting the STAT1 Pathway. (April 2020) - Cui, S.J.; Zhang, T.; Fu, Y.; Liu, Y.; Gan, Y.H.; Zhou, Y.H.; Yang, R.L.; Wang, X.D.
Severe inflammation, progressive cartilage, and bone destruction are typical pathologic changes in temporomandibular joint (TMJ) arthritis and lead to great difficulty for treatment. However, current therapy is inefficient to improve degenerative changes in progressive TMJ arthritis. This study investigated the therapeutic effects of human dental pulp stem cells (DPSCs) on severe inflammatory TMJ diseases. Progressive TMJ arthritis in rats was induced by intra-articular injection of complete Freund's adjuvant and monosodium iodoacetate. DPSCs were injected into the articular cavity to treat rat TMJ arthritis, with normal saline injection as control. Measurement of head withdrawal threshold, micro–computed tomography scanning, and histologic staining were applied to evaluate the severity of TMJ arthritis. Results showed that local injection of DPSCs in rats with TMJ arthritis relieved hyperalgesia and synovial inflammation, attenuated cartilage matrix degradation, and induced bone regeneration. Inflammatory factors TNF-α and IFN-γ were elevated in progressive TMJ arthritis and partially decreased by local injection of DPSCs. MMP3 and MMP13 were elevated in the arthritis + normal saline group and decreased in the arthritis + DPSCs group, which indicated amelioration of matrix degradation. The isolated primary synoviocytes were cocultured with DPSCs after inflammatory factors stimulated to explore the possible biological mechanisms. The expression of MMP3 and MMP13 in synoviocytes was elevated after TNF-α and IFN-γ stimulation and partially reversed by DPSC treatment in the in vitro study. The signal transducer and activator of transcription 1 (STAT1) was activated by inflammatory stimulation and suppressed by DPSC coculture. The upregulation of MMP3 and MMP13 triggered by inflammation was blocked by STAT1-specific inhibitor, suggesting that STAT1 regulated the expression of MMP3 and MMP13. In conclusion, this study demonstrated the possible therapeutic effects of local injection of DPSCs on progressive TMJ arthritis by inhibiting the expression of MMP3 and MMP13 through the STAT1 pathway.